2014
DOI: 10.2147/ijn.s57923
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of surface charge-modified ZnO nanoparticles with different particle sizes

Abstract: In this study, four types of standardized ZnO nanoparticles were prepared for assessment of their potential biological risk. Powder-phased ZnO nanoparticles with different particle sizes (20 nm and 100 nm) were coated with citrate or L-serine to induce a negative or positive surface charge, respectively. The four types of coated ZnO nanoparticles were subjected to physicochemical evaluation according to the guidelines published by the Organisation for Economic Cooperation and Development. All four samples had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…This pH is intermediate between the pKa of the GABA carboxyl and amine groups, and thus the GABA is expected to be neutral. The fact that the zeta potential studies show that ZnO NPs-GABA is in fact positively charged is similar to the result obtained by Kim et al [46], who functionalized ZnO NPs with L-serine and measured a zeta potential of +26.8 mV at pH 7.0. After ZnO NPs-GABA was covalently attached with CurBF2, this value shifted to −9.8 ± 0.5 mV.…”
Section: Zeta Potentialsupporting
confidence: 88%
See 2 more Smart Citations
“…This pH is intermediate between the pKa of the GABA carboxyl and amine groups, and thus the GABA is expected to be neutral. The fact that the zeta potential studies show that ZnO NPs-GABA is in fact positively charged is similar to the result obtained by Kim et al [46], who functionalized ZnO NPs with L-serine and measured a zeta potential of +26.8 mV at pH 7.0. After ZnO NPs-GABA was covalently attached with CurBF2, this value shifted to −9.8 ± 0.5 mV.…”
Section: Zeta Potentialsupporting
confidence: 88%
“…The pH solutions of all samples were determined as shown in Table S1. Wurtzite-type ZnO NPs are recognized to have positive surface charges in the as-prepared state [46]. The result showed that unmodified ZnO NPs showed zeta potential of 5.3 ± 1.1 mV while ZnO NPs modified by GABA demonstrated a zeta potential value of 24.9 ± 0.3 mV.…”
Section: Zeta Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…The monomodal dispersion observed after treatment is attributable to the size distribution of mono-dispersed n-ZnO particles (0.3–7 μm). The zeta potential of n-ZnO particles dispersed in ethanol was estimated as 26.3 ± 3 mV, which agrees well with the reference values of ZnO particles (24.0, 26.3 and 26.8 mV at pH 7) [ 9 , 10 ]. This positive and large zeta potential could facilitate homogenous dispersion of n-ZnO particles in polyimide and cured BMI matrices.…”
Section: Methodssupporting
confidence: 85%
“…Presence of -OH and C=O groups on the surface of CS make it hydrophilic in nature [38]. Herewith we propose that Zn 2+ produced during synthesis of ZnO using an aqueous solution of Zn(CH 3 COO) 2 can get coupled with such active sites especially where -OH group is present due to the electrostatic interactions [32,35,[39][40][41]. The Zn 2+ ions coupled at the surface of CS further reacts with the OH − ion present in the reaction solution to produce Zn(OH) 2 at the CS surface.…”
Section: Methodsmentioning
confidence: 98%